Perceptions of Practice Towards Management of Common Ailments In Indonesian Community Pharmacies: A Cross-Sectional Study - Mizranita, Vinci; Sakinatun Nisa, Fauziyyah (Devotion : Journal of Research and Community Service, 2024)
Managing common ailments is a growing service in developing countries. Community pharmacists and pharmacy technicians managing common ailments are essential for improving treatment outcomes. While common ailment services have been successfully implemented in developed countries, Indonesia needs more documentation of these practices. This study aimed to document the scopes of community pharmacists and pharmacy technicians in managing common ailments, their practices, and the perceived experience in providing these services. These cross-sectional surveys were conducted from May to June 2023 in separate pharmacists’ and pharmacy technicians’ seminars in Surakarta, Indonesia. Binary logistic regression compared the pharmacists' and pharmacy technicians' perceptions of managing ailments. A total of 180 pharmacists and 140 pharmacy technicians participated. Among 13 common ailments listed in the survey, acute pain (P<0.001) was an ailment that was perceived as limited to a pharmacist's scope. Ailments such as dandruff, constipation and mild headache were perceived to be within the scope of a pharmacy technician (P<0.001). Given the differing approaches by pharmacists and pharmacy technicians, there is a need to ensure that each professional practices within their area of scope.